5S implementation in warehouse for manufacture of plastic bottles factory - Lee, Soon Fui (2019)
5S is one of the most potent lean manufacturing tools, and the foundation of successful implementation is 5S. 5S is a simple tool for organizing your workplace in a clean, efficient, and safe way to increase productivity, visualize management, and ensure the introduction of standardization. In Hon Chuan Malaysia, their warehouse have not implement warehouse management. Their warehouse is messy and dirty. Due to this situation, the employees need to waste a lot of time for materials or finished goods. Besides that, when customer comes factory to visit or audit, this situation will give the customer a wrong impression. In addition, when the finished goods or materials is too much, there has no enough space for storage. The employees will put the finished goods and materials on the gangway. Otherwise, many finished goods and materials were stored for a long period in the warehouse until expired. For those items, it will be scrapped or disposed of. This project aims to implement 5S to keep the warehouse in a clean, efficient and safe manner with the objectives; 1) to study the 5S tools and techniques; 2) proposed the suitable 5S tools and techniques to be applied in the warehouse; 3) implement 5S tools and techniques in the warehouse. Therefore, 5S can make the warehouse clean and neat, eliminate waste in the warehouse, and improving company image.